Global trends in esophageal cancer. Issue 5 (20th March 2017) - Malhotra, Gautam K.; Yanala, Ujwal; Ravipati, Advaitaa; Follet, Matthew; Vijayakumar, M.; Are, Chandrakanth
Abstract : BACKGROUND AND OBJECTIVES: Esophageal Cancer (EC) is a lethal malignancy with poor prognosis and significant variations in the incidence, mortality, and histopathology based on geographic regions. The aim of this study was to quantitatively analyze these variations to identify patterns and areas for further research. METHODS: We utilized the GLOBOCAN 2012, and Cancer Incidence in five Continents, Volume X (CI5X) database to analyze variations in EC incidence and mortality. RESULTS: We found the EC incidence and mortality is geographically varied with a particularly high burden in East Asia and Eastern/Southern Africa where esophageal squamous cell carcinoma (SCC) predominates over adenocarcinoma (AC). Interestingly, there is a dichotomy between the high incidence of esophageal SCC in East Africa and low incidence in West Africa. The global incidence and mortality from EC is expected to rise in the coming decades. Asia, and China in particular, will continue to be the areas most burdened by EC, while Africa is expected to surpass the incidence and mortality rates of Europe. CONCLUSIONS: The global burden of EC is expected to rise in the coming years. Understanding the geographic, environmental, and genetic contributors to the development of EC will be essential in combating its prevalence.